Developmen of Hybrid Organizational Culture at Ar Rahmah Mosque Surabaya Indonesia - Abdullah Azzam; M. Syukur Ifansyah; Shobikhul Qisom; Ahmad Faiz Khudlari Thoha (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2025)
Masjid Ar Rahmah Surabaya adopts a hybrid organizational model that integrates Islamic values with modern management systems across four main sectors: da'wah, education, social services, and economy. This mosque functions not only as a place of worship but also as a center for community empowerment, implementing various programs based on Islamic principles. This study aims to analyze organizational culture development strategies that maintain synergy among units without causing fragmentation or internal conflicts. Using a qualitative approach, this research applies Edgar Schein’s theory to identify organizational culture at three levels: artifacts, espoused values, and underlying assumptions. The findings indicate that the implementation of the KHIDMAH culture (Collaborative, Humanistic, Integrity, Dedication, Moderate, Adaptive, Harmonious) plays a crucial role in fostering a productive, sustainable, and cohesive work environment. Strategies such as strengthening a shared vision, enhancing human resource synergy, implementing complementary practices among units, and promoting continuous organizational learning ensure that each unit contributes effectively toward the mosque’s grand mission: producing mosque imams at the Asia-Pacific level. With this model, Masjid Ar Rahmah has successfully become financially independent while serving as a center for da'wah and community empowerment, achieving a strong competitive position both nationally and internationally.